THE DEVELOPMENT OF INSTRUCTION BOOK ABOUT ARCHIPELAGO CAKE MAKING IN STUDY OF COOK AND FOOD PREPARATION FOR STUDENTS WITH HEARING IMPAIRMENT - Dienda Nurmaisitha; S Sudarsini (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purpose of this research was to develop instruction book of archipelago cake making for students with hearing impairment. The research adapted the Sugiyono (2011) model which consists of 7 stages: (1) potential problems, (2) data collection, (3) product design, (4) validation of the design, (5) design revisions, (6) product testing, and (7) the revision of the product. The results of matter experts was 97%, media experts was 92%, and practitioners (teachers) was 98%. The individual experimental result was 90% for student I, 95% for student II, and 80% for student III. The result of field experimental from the evaluation to the students were 82,66 in average scoring. The research result showed that the instruction book about archipelago cake making in study of cook and food preparation for students with hearing impairment in state SMPLB was proper and effective.